"Locking the Head Technique" For Femoral Head Removal in Intracapsular Neck Femur Fractures. Issue 3 (September 2021) - Ansari, Naved F.; Sonawane, Dhiraj; Mehta, Ajit K.; Pawar, Eknath
Abstract : Background: Intracapsular neck femur fractures are one of the most commonly operated fractures. Head excision is done with engagement of corkscrew, which is a difficult step especially in subcapital type of fractures as the head femur rotates and spins while engaging the corkscrew and slips off and thereby requiring multiple attempts for corkscrew engagement and risking the head with a cut through and damage to the head and the acetabulum. We have a simple technique which can make engaging the corkscrew in the head easier and thereby making the femoral head removal easier and safer. Technique: Using a 2 mm guide wire placed in the head after exposure and Locking the Head, to stabilize it before placing the corkscrew then engaging the corkscrew firmly and removing the head with crockscrew with ease. Discussion: Improves accuracy of corkscrew fitting in the head and retaining the contour of the head and thereby easing the removal of the head and making the technique easier. Abstract : Supplemental Digital Content is available in the text.